PENGARUH DISIPLIN, PROFESIONALISME DAN KARAKTERISTIK GURU TERHADAP KINERJA GURU SEKOLAH DASAR (SD) Se-KECAMATAN STABAT KABUPATEN LANGKAT - Sagino . (Manajemen dan Bisnis, 2020)
The problem formulation in this research is: how to influence the discipline on the teacher's performance, how the professional influence on the teacher's performance in elementary School (SD) Se – District Stabat Langkat District. How the teacher's characteristic influence on the teacher's performance in elementary School (SD) Se – Kecamatan Stabat, Langkat District, how to simultaneously influence the discipline, professionalism and characteristics of teachers on teachers ' performance in elementary School (SD) Se – District of Stabat, Langkat district. The results of the study were obtained that there was a significant influence on the discipline variable impact master performance with the value of Thitung This (4,708 1,995). Professionalism variable has a significant effect on Guru performance with the value of Thitung This (2,391 1,995), characteristic variables have significant effect on Guru performance with the value of Thitung This (3,988 1,995), discipline variables, Professionalism, the characteristics of positive and significant effect on the performance of teachers in elementary School (SD) Se-Kecamatan Stabat District Langkat. Of 41.3%, while the remaining of 58.7% (100%-41.3%) Influenced by other factors not researched.